2023
DOI: 10.18502/jovr.v18i1.12731
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-ophthalmic Manifestations of Coronavirus Disease 2019 and Its Vaccination: A Narrative Review

Abstract: Coronavirus disease 2019 (COVID-19) is a current pandemic caused by SARS-CoV-2 that has vastly affected the whole world. Although respiratory disease is the most common manifestation of COVID-19, the virus can affect multiple organs. Neurotropic aspects of the virus are increasingly unfolding, in so far as some respiratory failures are attributed to brainstem involvement. The neuro-ophthalmic manifestations of COVID-19 and the neuro-ophthalmic side effects of vaccination were reviewed. The major findings are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 91 publications
0
9
0
1
Order By: Relevance
“…Tonic pupils or Horner syndrome were also noted as a neuro-ophthalmic manifestation in 4 patients with COVID-19 123–127 . Tonic pupils were reported to develop after COVID-19 infection with sluggish pupillary reaction to light with vermiform movement and segmental constriction.…”
Section: Neuro-ophthalmic Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tonic pupils or Horner syndrome were also noted as a neuro-ophthalmic manifestation in 4 patients with COVID-19 123–127 . Tonic pupils were reported to develop after COVID-19 infection with sluggish pupillary reaction to light with vermiform movement and segmental constriction.…”
Section: Neuro-ophthalmic Manifestationsmentioning
confidence: 99%
“…Tonic pupils or Horner syndrome were also noted as a neuro-ophthalmic manifestation in 4 patients with COVID-19. [123][124][125][126][127] Tonic pupils were reported to develop after COVID-19 infection with sluggish pupillary reaction to light with vermiform movement and segmental constriction. Notably, near response was also impaired in reported cases of tonic pupils contrary to the typical presentation in noninfectious cases, 123,124 and the diagnosis was confirmed by hypersensitivity to 0.1% pilocarpine with pupillary constriction in the affected eyes.…”
Section: Pupillary Abnormalitiesmentioning
confidence: 99%
“…In these cases, patients were reported to develop a gradual loss of vision one to two weeks after severe COVID infection unilaterally or bilaterally; females tended to suffer from ON and retinal complications. [ 56 , 57 , 63 ]…”
Section: Introductionmentioning
confidence: 99%
“…
We read with interest the narrative review by Feizi et al about the neuro-ophthalmologic complications of SARS-CoV-2 infections and vaccinations. [1] It was concluded that SARS-CoV-2 infections and all SARS-CoV-2 vaccines can affect the afferent and efferent visual pathways due to papillophlebitis, idiopathic intracranial, hypertension, optic neuritis, ischemic stroke, pupillomotor pathway impairment, and cranial nerve dysfunction. [1] The study is comprehensive, but has limitations that are a cause for concern and should be discussed.Headaches should not always be classified as the neuro-ophthalmologic manifestation of SARS-CoV-2 infections or vaccinations.
…”
mentioning
confidence: 99%
“…[1] It was concluded that SARS-CoV-2 infections and all SARS-CoV-2 vaccines can affect the afferent and efferent visual pathways due to papillophlebitis, idiopathic intracranial, hypertension, optic neuritis, ischemic stroke, pupillomotor pathway impairment, and cranial nerve dysfunction. [1] The study is comprehensive, but has limitations that are a cause for concern and should be discussed.Headaches should not always be classified as the neuro-ophthalmologic manifestation of SARS-CoV-2 infections or vaccinations. Headache, though regarded as one of the most common…”
mentioning
confidence: 99%